Outcome of twin‐to‐twin transfusion syndrome in monochorionic monoamniotic twin pregnancy: systematic review and meta‐analysis. (2nd March 2020) - Murgano, D.; Khalil, A.; Prefumo, F.; Mieghem, T. Van; Rizzo, G.; Heyborne, K. D.; Melchiorre, K.; Peeters, S.; Lewi, L.; Familiari, A.; Lopriore, E.; Oepkes, D.; et al.
ABSTRACT: Objectives: To explore the outcome of monochorionic monoamniotic (MCMA) twin pregnancies affected by twin‐to‐twin transfusion syndrome (TTTS). Methods: MEDLINE and EMBASE databases were searched for studies reporting the outcome of MCMA twin pregnancies complicated by TTTS. The primary outcome was intrauterine death (IUD); secondary outcomes were miscarriage, single IUD, double IUD, neonatal death (NND), perinatal death (PND), survival of at least one twin, survival of both twins and preterm birth (PTB) before 32 weeks' gestation. Outcomes were assessed in MCMA twins affected by TTTS not undergoing intervention and in those treated with amniodrainage, laser therapy or cord occlusion. Subgroup analysis was performed including cases diagnosed before 24 weeks. Random‐effects meta‐analysis of proportions was used to analyze the data. Results: Fifteen cohort studies, including 888 MCMA twin pregnancies, of which 44 were affected by TTTS, were included in the review. There was no randomized trial comparing the different management options in MCMA twin pregnancies complicated by TTTS. In cases not undergoing intervention, miscarriage occurred in 11.0% of fetuses, while the incidence of IUD, NND and PND was 25.2%, 12.2% and 31.2%, respectively. PTB complicated 50.5% of these pregnancies. In cases treated by laser surgery, the incidence of miscarriage, IUD, NND and PND was 19.6%, 27.4%, 7.4% and 35.9%, respectively, and the incidence of PTB before 32 weeks' gestation was 64.9%. In cases treated with amniodrainage, the incidence of IUD, NND and PND was 31.3%, 13.5% and 45.7% respectively, and PTB complicated 76.2% of these pregnancies. Analysis of cases undergoing cord occlusion was affected by the very small number of included cases. Miscarriage occurred in 19.2%, while there was no case of IUD or NND of the surviving twin. PTB before 32 weeks occurred in 50.0% of these cases. Conclusions: MCMA twin pregnancies complicated by TTTS are at high risk of perinatal mortality and PTB. Further studies are needed in order to elucidate the optimal type of prenatal treatment in these pregnancies. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.